2019
DOI: 10.21638/spbu03.2019.205
|View full text |Cite
|
Sign up to set email alerts
|

The genes determining synthesis of pigments in cotton

Abstract: Naturally coloured cotton is environmentally friendly, since bleaching and chemical dyeing are not needed during textile production. Studying moleculargenetic mechanisms underpinning pigment production may facilitate breeding cotton with coloured fibre. In the current review we summarize the known data on structural and regulatory genes involved in biosynthesis of flavonoid pigments proanthocyanidins (PAs) in brown and caffeic acid (CA) derivates in green fibre. The first chapter considers the first studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Flavonoids are well-known to play a wide range of biological activities in plant UV protection, flower coloration, antioxidant, antibacterial, anti-inflammatories, anti-cancer and antifungal properties, and defense [ 27 ]. Contrary to brown color formation, PAs also have antioxidant and anti-inflammation activities [ 13 ]. NBCC biological activities are understudied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flavonoids are well-known to play a wide range of biological activities in plant UV protection, flower coloration, antioxidant, antibacterial, anti-inflammatories, anti-cancer and antifungal properties, and defense [ 27 ]. Contrary to brown color formation, PAs also have antioxidant and anti-inflammation activities [ 13 ]. NBCC biological activities are understudied.…”
Section: Discussionmentioning
confidence: 99%
“…In Petunia, floral anthocyanin pigmentation patterns expression patterns were reported to be determined by R2R3-MYB and bHLH activators. In addition, R2R3-MYB proteins activated early anthocyanins and PA biosynthetic genes [ 13 ]. Moreover, some reports have confirmed that MYB encoding TT2 homolog gene GhTT2-3A controls PA biosynthesis and dark brown pigmentation in cotton fiber coloration, and high-level expression of GhTT2_A07 results in the up-regulation of the PA pathway [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation